Peningkatan Pengetahuan Masyarakat Kecamatan Anduonohu Kota Kendari Mengenai Cara Penggunaan Sediaan Obat Khusus: Peningkatan Pengetahuan Masyarakat Kecamatan Anduonohu Kota Kendari Mengenai Cara Penggunaan Sediaan Obat Khusus - A Sida, Nurramadhani (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
Public understanding of the proper use of medications is a crucial foundation for achieving optimal health. However, in reality, many people still do not understand how to properly use specific drug formulations. Therefore, this community service aims to provide comprehensive information on how to use special drug formulations, particularly those frequently used by the public, such as eye drops, ear drops, nasal drops, eye ointments, and suppositories. The service was carried out at the Callista Farma Clinic and Pharmacy, involving 30 community members. The method of delivery was through a lecture using leaflets as media. Pretests and posttests were conducted to assess initial knowledge and the success of the education. The pretest results showed that the majority of participants (86%) fell into the low to moderate category (0-10 correct answers). Only 4 participants (13%) showed a good level of knowledge (11-15 correct answers). This indicates that information about how to use special drug formulations is necessary. Education was directly provided to the community regarding the proper use of medications with special formulations such as eye drops, ear drops, nasal drops, eye ointments, and suppositories, in accordance with the Ministry of Health regulations. The success of the education was measured with the posttest, which showed a sharp increase in the number of participants with high scores (11-15) to 22 people (73%). The increase in posttest scores indicates that the educational activities had a positive impact on the participants' understanding of how to use special drug formulations. Education can enhance the public's knowledge of how to properly use these specific drug formulations.